L’ethos collectif des altermondialistes dans les forums sociaux mondiaux - Azzedine Kadir (Multilinguales)
The alterglobalist movement is part of the constellation of forms of citizen mobilization that today seem to be preferred by alterglobalists who are increasingly abandoning traditional forms of struggle. Born in the late nineties, the world social forums are today spread all over the world, especially in the USA, in the countries of South America and in Africa. Our article will therefore analyze the construction of the self-image that was carried out in the altermondialist discourse and the way in which it was established through a polarization between globalization and alterglobalization. Because of the argumentative aim of this construction, we resort to the notion of collective ethos, namely the self-image that the speaker builds through his speech to exert an influence on his audience.